P33-04 Investigating chemical systemic toxicity in the food industry: A NGRA approach - Basili, D.; Reale, E.; Coulet, M.; Stroheker, T.; Brinon, B.; Ratinaud, Y.; Holzwarth, J.; Descombes, P.; Guitard, M.; Panchaud, A.; Montoya, G. (Toxicology letters, 2025)
Chemical risk assessment is undergoing a significant transformation thanks to the fast pace of technological advancement which enable hazard and exposure characterization leveraging high-throughput assays with the ability to deliver mechanistic understanding, without relying on animal models. This prompted the development of the so called Next-Generation Risk Assessment (NGRA) a conceptual framework leveraging hazard related bioactivity data, in combination with internal human exposure, to derive thresholds protective of human health. Development of AOPs has been pivotal in characterizing the bioactivity of chemicals for which mode of action are known. However, global production of chemicals is expected to double by 2030 due to the rapid increase in the use across sectors and a more general approach investigating systemic toxicity is needed to successfully assess the risk of these compounds lacking toxicological characterization. Such approach, relies on gathering bioactivity data by integrating multiple NAMs that ensure a good biological coverage. Integration of NAMs to explore systemic toxicity has been successfully applied in the cosmetics industry, as a consequence of the 2013 European ban on animal testing. Application of such approach in the food industry is limited due to current regulatory requirements with regards to animal testing however, the regulatory landscape across all sectors is set to change in the coming years driven by scientific development. In this context we set to explore whether a NGRA approach to systemic toxicity would be successful to drive decision-making. To this extent a NAMs toolbox building up on knowledge already available in the public domain was assembled including NAMs covering 1) cellular stress responses, 2) a fully human-based in vitro pharmacological profiling (IPP) and 3) transcriptomic profiling across three cell lines. Data collected from these assays were mined to derive points of departure (PoDs) that were integrated with Physiologically-Based Kinetic (PBK) modelling estimates of internal exposure to derive Bioactivity-Exposure Ratios (BER). Food-relevant chemicals covering different classes including contaminants, food additives, pesticides and naturally occurring constituents, for which safety level may or may not be available, were investigated to assess whether a low tier approach could support safety decisions. By deriving the chemical BER and benchmarking it against established human safety levels, when available, we demonstrate the ability of the NGRA framework to drive safety decisions without animal testing. Importantly, this work also shed light on the need for refinement of the toolbox to make it more food-relevant hence setting the scene for future activities.